2018
DOI: 10.1089/dna.2017.4033
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing of Kinase Inhibitors as Broad-Spectrum Antiviral Drugs

Abstract: The high cost of drug development and the narrow spectrum of coverage typically provided by direct-acting antivirals limit the scalability of this antiviral approach. This review summarizes progress and challenges in the repurposing of approved kinase inhibitors as host-targeted broad-spectrum antiviral therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
67
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 71 publications
0
67
0
1
Order By: Relevance
“…Anti-malaria quinolones (chloroquine and hydroxychloroquine) inhibit acidification of endosomes, which is an essential process for uncoating of ssRNA viruses (Al-Bari, 2017). Anticancer kinase inhibitors dasatinib, imatinib, gefitinib, nilotinib, erlotinib and sunitinib impair intracellular viral trafficking and exert BSA effects (Bekerman et al, 2017;Schor and Einav, 2018). The anti-Duchenne muscular dystrophy agent, alisporivir, targets cellular cyclophilin and inhibits the folding of HCV, HIV, MERS-and SARS-CoV proteins, and, therefore, prevents formation of infectious virus particles (Boldescu et al, 2017;de Wilde et al, 2017;Soriano et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Anti-malaria quinolones (chloroquine and hydroxychloroquine) inhibit acidification of endosomes, which is an essential process for uncoating of ssRNA viruses (Al-Bari, 2017). Anticancer kinase inhibitors dasatinib, imatinib, gefitinib, nilotinib, erlotinib and sunitinib impair intracellular viral trafficking and exert BSA effects (Bekerman et al, 2017;Schor and Einav, 2018). The anti-Duchenne muscular dystrophy agent, alisporivir, targets cellular cyclophilin and inhibits the folding of HCV, HIV, MERS-and SARS-CoV proteins, and, therefore, prevents formation of infectious virus particles (Boldescu et al, 2017;de Wilde et al, 2017;Soriano et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Mounting evidence have shown that viruses hijack a variety of human kinases throughout the entire viral life cycle to facilitate their replications, and some kinases are broadly required. [109][110][111] Therefore, it can be anticipated that the inhibition of such kinases would lead to the disruption of a broad spectrum of viral replications. Since tremendous kinase inhibitors have been approved in clinic for treating cancer and inflammatory diseases, and more are under development in the pipelines, increasing efforts have been devoted to repurposing approved kinase inhibitors as broad-spectrum antiviral agents.…”
Section: Kinasesmentioning
confidence: 99%
“…Many other kinases are also involved and play essential roles in different life cycle of various viruses, and their corresponding kinase inhibitors show broad-spectrum antiviral activities against a wide range of viruses both in vitro and in vivo. [109][110][111] Since host kinase is not under the genetic control of virus, kinase inhibitors for antiviral treatment have much higher genetic barrier to resistance. For example, DENV developed resistance against the viral NS4B inhibitor SDM25N after eight passages, yet it remained sensitive to the treatment of 49 and 50 under the same conditions.…”
Section: Kinasesmentioning
confidence: 99%
“…Due to all these reasons, we urgently need new, efficient, broadspectrum antivirals (Howard and Fletcher, 2012;Schor and Einav, 2018). The traditional strategy in drug development of one virus one drug, based in the development of molecules that specifically target a viral protein, has been very successful for certain viruses like HIV or hepatitis C virus (HCV) (Barre-Sinoussi et al, 2013;Li and De Clercq, 2017).…”
Section: Introductionmentioning
confidence: 99%